Lens of war : exploring iconic photographs of the Civil War - Gallagher, Gary W. (Uncivil Wars, 2015)
Introduction / J. Matthew Gallman and Gary W. Gallagher -- Part I. Leaders -- The "Gettysburg" Lincoln: the back story of a full-frontal photograph / Harold Holzer -- Robert E. Lee and Traveller in Petersburg / Ethan S. Rafuse -- "It is just what it is and nothing else": Grant after Cold Harbor / Joan Waugh -- Jeb Stuart in full finery / Gary W. Gallagher -- Roads to Antietam: George McClellan, Abraham Lincoln, and Alexander Gardner / J. Matthew Gallman -- The weird one: Stonewall Jackson's Chancellorsville portrait / Kathryn Shively Meier -- The peculiar genius of William Tecumseh Sherman / Joseph T. Glatthaar -- Part II. Soldiers -- Looking at war: Union soldiers in the Peninsula Campaign / Aaron Sheehan-Dean -- Cary Robinson's last Christmas / Emory M. Thomas -- Confederates at Gettysburg / Brooks D. Simpson -- Champ Ferguson / Daniel E. Sutherland -- Who are they? / Carol Reardon -- Part III. Civilians -- A family in camp / Caroline E. Janney -- What's in a face: Annie Etheridge Hooks and civil work / Jane E. Schultz -- Refugee camp at Helena, Arkansas, 1863 / Thavolia Glymph -- Finding a new war in an old image / Susan Eva O'Donovan -- Part IV. Victims -- My dead Confederate / James Marten -- Andrew J. Russell and the stone wall at Fredericksburg / Earl J. Hess -- "A harvest of death": negative by Timothy O'Sullivan, positive by Alexander Gardner / Stephen Cushman -- Colonel William P. Rogers and his comrades: postmortem at Corinth, Mississippi, October 1862 / T. Michael Parrish -- "Eye of history": looking at Civil War prisoners of war / Judith A. Giesberg -- A dead horse / James I. Robertson Jr -- Part V. Places -- City Point, Virginia: the nerve center of the Union war effort / Elizabeth R. Varon -- The book or the gun? / Stephen Berry -- From home front to ruins: the Fredericksburg destruction / William A. Blair -- George N. Barnard, "Charleston, S.C. view of ruined buildings through porch of the Circular Church (150 Meeting Street)," 1865 / Megan Kate Nelson -- The Grand Review / Steven E. Woodworth.